A4.15 Osteoporosis knowledge, self-efficacy, and health beliefs among chinese men and women with HIV. (31st January 2014) - Hsieh, Evelyn; Fraenkel, Liana; Bradley, Elizabeth; Xia, Weibo; Qu, Cui; Ling, Luo; Insogna, Karl; Li, Taisheng
Abstract : Background and Objectives: Prior studies demonstrate increased rates of osteoporosis and fracture among patients with HIV. Validated scales exist for measuring osteoporosis-related knowledge, self-efficacy for behavioural change, and health beliefs, but have not yet been applied to HIV-infected populations. Better understanding of these factors can increase the effectiveness of osteoporosis prevention efforts. Materials and Methods: Subjects were drawn from a multi-center trial in China comparing 3 antiretroviral regimens. Volunteers completed a questionnaire with 6 sections including: 1. Fracture risk assessment, 2. International Physical Activity Questionnaire (IPAQ), 3. Calcium and vitamin D intake scale, 4. Osteoporosis Knowledge Test (OKT), 5. Osteoporosis Self-Efficacy Scale (OSES), and 6. Osteoporosis Health Beliefs Scale (OHBS). Demographic data were obtained from the parent study. Results: In total 263 subjects participated (200 men, 63 women). Mean age (38.4 ± 9.8 yrs.) and BMI (21.6 ± 2.6 kg/m 2 ) were similar for both sexes. Men were more likely to have completed high school (69 v. 23.8%, p = 0.000) and report smoking (49 v. 8.8%, p = 0.000) or alcohol use (26.8 v. 12.3%, p = 0.022) than women. Moderate physical activity level was most common for both sexes (41.8 v. 44.6%, p = 0.931) and mean frequency of consumption of calcium and vitamin D-rich foods was similar in both groups (p = 0.257). OKT calcium and exercise scores were low for both groups, yet OSES calcium and exercise scores reflected moderate confidence regarding ability to adopt behavioural change. Subjects did not perceive personal susceptibility to osteoporosis and felt neutral regarding the seriousness of a diagnosis of osteoporosis. Both men and women recognised benefits of exercise and calcium intake, however men were less likely to perceive barriers to exercise and calcium intake compared with women. Both sexes reported moderate overall health motivation. Multiple regression analysis showed that higher intake of calcium and vitamin D rich foods was associated with higher OKT calcium score (β = 0.29, 95% CI 0.01 to 0.58, p = 0.043) and OSES calcium score (β = 0.07, 95% CI 0.03 to 0.11, p = 0.001), whereas higher physical activity level correlated with lower education (β = 0.45, 95% CI 0.25 to 0.81, p = 0.008). Conclusions: Knowledge regarding osteoporosis is low among Chinese men and women with HIV, and women perceive more barriers to behavioural change than men. Calcium and vitamin D intake and physical activity levels have different predictors. Understanding these associations may aid in the development of targeted behavioural interventions for this vulnerable group.